Regulation of Electronic Media in Pakistan, the US and the UK (Journal of Governance and Development (JGD), 2018)
Regulation of electronic media is a vital aspect of freedom of expression of electronic media. However, in Pakistan it is alleged that freedom of expression is heavily regulated and there is very little space for freedom of expression on electronic media. This article examines this assertion of heavy regulation by comparing the regulatory systems of Pakistan with regulatory systems of England and America. Comparative legal research method is used under this study. Comparative legal research method is supported by the socio legal method of research. Under socio legal methods, three legal experts were interviewed, for expert opinion on the matter. This article concludes that Pakistan lacks in several key areas of regulation of electronic media as compared to the USA and UK. At the end this article presents future implications regarding regulation of electronic media.